From Mexicas to Ancient Aztecs, Classical Nahuas, and Modern Indios/as: Early Modern Criollo/a Constructions and Understandings of Indigenous New Spain - Hugo Daniel Peralta-Ramírez:::::: (2024)
Scholars have written extensively on visual representation of Indigenous Peoples in Mesoamerica. (Post)Conquest woodprints of Indigenous Peoples depicted White or Black Legends. Casta paintings of the colonial period illustrated notions of racial/ethnic social organization and differentiation. The CSUSM Library Award for Undergraduate Research, Scholarship and Creative Activity recognizes undergraduate students who demonstrate sophistication and originality in research projects and creative works, and reflection upon the research/creation process. Up to six prizes will be awarded in three categories: Creative Works, Empirical Research and Interpretive Analysis. Winners receive a cash prize and public recognition of their excellent work. Submissions by individuals or groups will be considered in the following three categories: Creative Works, including, but not limited to, an art installation, software program, musical composition, film or video, special project, etc. Empirical Research, including, but not limited to, research conducted with qualitative or quantitative methodologies using the (social-) scientific method. Interpretive Analysis, including, but not limited to, analysis which aims to capture hidden meaning and ambiguity of a cultural artifact.